Analisis Kepercayaan Konsumen Sewa Kos dan Kontrakan di Facebook pada Mahasiswa Universitas Islam Negeri Walisongo Semarang - Vika Safitri Rahmayuniar; Elsa Sabina Putri Latifah; Irgi M. Aqil Daeng Masiga; Khairani Zikrinawati; Zulfa Fahmy (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Consumer trust is one of the doors to the success of an online transaction. Consumer’s trust is needed, one of which is in boarding and renting for overseas students who’s in need a place to live in. Facebook is one of the social media that provides information about boarding houses and rent. Consumer’s trust regarding the information available needs to be fulfilled because the place of residence is the main thing. The purpose of this study is to analyze consumer trust regarding boarding and rent information on Facebook. This study uses a qualitative approach with a focused group discussion method that takes place on Google Meet. The subjects of this study were 11 students of UIN Walisongo Semarang. This research was conducted for 3 months. This study uses internal validity, external validity, reliability and objectivity for Data analysis technique. The results of the research show that the factors of consumer’s trust are more information distribution, open communication to consumers, and alignment between information and reality. From the results of this study, it is recommended to conduct a direct survey first before deciding to rent a boarding house or rented house to increase trust regarding the boarding house and rented house on Facebook.